Changes of cortical interhemispheric responses after status epilepticus in immature rats - Mares, Pavel; Tsenov, Grygoriy; Aleksakhina, Katarina; Druga, Rastislav; Kubová, Hana (Epilepsia, 2005)
PURPOSE: To study cortical excitability after status epilepticus induced in two age groups of immature rats. METHODS: Lithium-pilocarpine status epilepticus was elicited in 12- (SE12) or 25-day-old (SE25) rats. Control siblings received saline instead of pilocarpine. Interhemispheric responses were elicited by stimulation of sensorimotor region of cerebral cortex 3, 6, 9, 13, or 26 days after status. Single biphasic pulses with intensities from 0.2 to 4 mA were used for stimulation; eight responses were always averaged. Amplitude of the first positive and negative waves (i.e., monosynaptic transcallosal responses) was measured and used for construction of input-output (I/O) curves. FluoroJade B was used to visualize degenerating neurons 24 h after status in both age groups. RESULTS: No significant changes were found at short intervals, but only a tendency to lower amplitudes 3 days after status in SE12 group. Marked changes appeared 26 days after status. The younger group exhibited lower amplitudes than did control rats, whereas SE25 animals generated responses with higher amplitude than did controls (i.e., the I/O curve was steeper. FluoroJade B-positive neurons were scarce in SE12 rats, whereas a substantial number of positive neurons was found in SE25 animals. The positive neurons exhibited characteristics of interneurons, and their distribution in cortical layers differed in the two groups. CONCLUSIONS: Status epilepticus resulted in neuronal death in both SE12 and SE25 animals. Changes in transcallosal evoked potentials were opposite in the two age groups. Augmented amplitude of responses in SE25 rats may indicate an increased cortical excitability.
Keywords: Interneurons; Fluorescent Dyes; Male; Rats, Wistar; corpus callosum; elektrická stimulace; Lithium Chloride; Organic Chemicals; mozková kůra; Nerve Degeneration; Electric Stimulation; organické látky; mužské pohlaví; potkani Wistar; interneurony; pilokarpin; status epilepticus; krysa rodu Rattus; Pilocarpine; degenerace nervu; fluoresceiny; Animals; Status Epilepticus; zvířata; chlorid lithný; Functional Laterality; Rats; Corpus Callosum; fluorescenční barviva; Fluoresceins; funkční lateralita; Cerebral Cortex